Increasing Inclusion or Expanding Exclusion? How the Global Strategy to Include Refugees in National Education Systems Has Been Implemented in Lebanon - Kelcey, Jo; Chatila, Samira (Refuge, 2020)
The UNHCR strategy to include refugee students in host state education systems is intended to promote refugees’ access to quality education. However, numbers of out-of-school refugees far exceed the global average. To understand these persistent barriers, we examine how Lebanese teachers and school principals understand and enact inclusion for school-age Syrian refugees. We find that inclusion has been pursued in ways that reproduce education inequities in Lebanon. Our findings underscore the importance of account- ing for the internal complexities that shape the implementation and appropriation of policies within refugee host states and the ways in which these complexities interact with aid structures.